Effect of β − hydroxy − γ -aminophosphonate (β − HPC) on the hydrolytic activity of Nocardia brasiliensis as determined by FT−IR spectrometry - Martínez-Robles, Sandra; González-Ballesteros, Erik; Reyes-Esparza, Jorge; Trejo-Teniente, Isaí; Jaramillo-Loranca, Blanca Estela; Téllez-Jurado, Alejandro; Vázquez-Valadez, Víctor H.; Angeles, Enrique; Vargas Hernández, Genaro (Frontiers in Microbiology, 2023)
The use of immunomodulatory and metabolic modulating drugs has been considered a better strategy to improve the efficacy of conventional treatments against pathogens and metabolic diseases. L-carnitine is relevant in fatty acid metabolism and energy production by β-oxidation, but it also has a beneficial therapeutic immunomodulatory effect. The β-hydroxy-γ-aminophosphonate (β-HPC) was developed, synthesized and studied in different pathologies as a more soluble and stable analog than L-carnitine, which has been studied in bacterial physiology and metabolism; therefore, we set out to investigate the direct effect of β-HPC on the metabolism of N. brasiliensis, which causes actinomycetoma in Mexico and is underdiagnosed. To analyze the effect of β-HPC on the metabolic capacity of the bacterium for the hydrolysis of substrate casein, L-tyrosine, egg yolk, and tween 80, Fourier transform infrared spectroscopy (FT-IR) was employed. It was found that β-HPC increases the metabolic activity of N. brasiliensis associated with increased growth and increased hydrolysis of the substrates tested. By the effect of β-HPC, it was observed that, in the hydrolysis of L-tyrosine, the aromatic ring and functional groups were degraded. At 1515 cm–1, any distinctive signal or peak for this amino acid was missing, almost disappearing at 839, 720, 647, and 550 cm–1. In casein, hydrolysis is enhanced in the substrate, which is evident by the presence of NH, OH, amide, and CO. In casein, hydrolysis is enhanced in the substrate, which is evident by the presence of NH, OH, amide, COO, and P = O signals, characteristic of amino acids, in addition to the increase of the amide I and II bands. In Tween 80 the H-C = and C = C signals disappear and the ether signals are concentrated, it was distinguished by the intense band at 1100 cm–1. Egg yolk showed a large accumulation of phosphate groups at 1071 cm–1, where phosvitin is located. FT-IR has served to demonstrate that β-HPC is a hydrolysis enhancer. Furthermore, by obtaining the spectrum of N. brasiliensis, we intend to use it as a quick comparison tool with other spectra related to actinobacteria. Eventually, FT-IR may serve as a species identification option.